The role of guilt appeals on donation behavior - Lwin, Michael; Phau, Ian (International Management Development Association, 2011)
This study explores the relationships between existential guilt, attitude towards the brand, inferences of manipulative intent (IMI) and actual donation behaviour. World Vision advertisement was used as the stimulus and the results show a positive relationship between existential guilt and actual donation behaviour. Interestingly, attitude towards the brand did not increase the likelihood of donations. IMI did not moderate the relationship between existential guilt and actual donation behavior. The research suggests that existential guilt appeals are appropriate for the charitable advertisements and it shows a direct link between guilt and actual donation behavior.